Clinical Characteristics and In-Hospital Outcomes of STEMI Patients Admitted during the SARS-CoV-2 Pandemic – an Observational Comparative Study - M, Baumhardt; M, Rattka; J, Dreyhaupt; K, Thiessen; S, Markovic; D, Buckert; J, Mörike; LM, Schneider; B, Gonska; D, Scharnbeck; A, Pott; M, Keßler; et al. (Cardiology and Cardiovascular Medicine, 2021)
Background: During the ongoing SARS-CoV-2 pandemic, a significant decline in acute coronary syndromes (ACS) including ST segment elevation myocardial infarction (STEMI) has been reported from several countries. Studies on the effect of the pandemic itself and measures of social restriction on clinical presentation and outcome of STEMI patients are contradictive. Methods: 103 consecutive STEMI patients admitted to our clinic between November 21st, 2019 and May 20th, 2020 were divided into a pre-pandemic cohort (62 patients, November 21st -March 20th, 2020), and a pandemic cohort (41 patients, March 21st - May 20th, 2020). Clinical presentation, in-hospital complications, outcome, laboratory data, and procedural characteristics of acute percutaneous coronary interventions (PCI) between the cohorts were compared. Results: Compared to the pre-pandemic period patients in the pandemic cohort had higher peak high sensitivity troponin T (2903ng/l, interquartile range IQR 9->10000ng/l vs. 3967ng/l, IQR 289->10000ng/l, p=0.04), more often a TIMI flow <3 at the end of the revascularization procedure (8% vs. 34%, p<0.01), were more often treated with tirofiban (3% vs. 29%, p<0.01), stayed longer on ICU (1.06 vs. 2.39 days, p=0.02), and had more in-hospital complications (16% vs. 39%, p=0.01). Conclusion: Presumably due to a delay in seeking acute medical care during the SARS-CoV-2 pandemic, patients with STEMI presented with higher troponin, worse restoration of coronary flow after acute PCI and suffered from more in-hospital complications compared to previous months. Public awareness for life-threatening diseases such as ACS has to be maintained to ensure adequate medical care for all patients during the SARS-CoV-2 pandemic.